Application of group technology in complex cluster type organizational systems - Morača, Slobodan (Strojniški vestnik, 2010)
The aim of this research was to contribute to the development of structural design procedures of complex - cluster type organizational systems. Industrial clusters can help companies to improve their own market positions, effectiveness, productivity and product quality. Organization of the production process in a company is an extremely complex process itself, and when it is transferred to the cluster level, the result is a complex task which is difficult to solve. For that purpose, this paper analyses the conditions and possibilities that would enable those structures to adapt to changes in the surroundings - flexibility and management adequacy of production and organizational structures - by lowering the degree of complexity. For the time being, no simple models which would enable an increase of process effectiveness in complex organizational units like clusters have been developed. One of the possible solutions which would decrease the complexity of flows and increase process effectiveness within an industrial cluster is the application of Group approach.
Keywords: industrijski grozdi; management; načrtovanje; podjetništvo